Association between hamstrings eccentric strength and sprint performance in football players - Brunn, D.; Líška, D.; Švantner, R.; Franek, V.; Sýkora, J.; Pupiš, M. (SportMont, 2022)
Sprint is essential for successful sport performance. Acceleration is necessary for every position in football. The ability to successfully accelerate is also an important determinant for more carried gaming activities. The eccentric strength of the hamstrings is an important task in sprint. The aim of our study was to test the correlation between the 30 m sprint and the eccentric strength of the hamstring by NordBord. The sample consisted of 48 professional football players (23.15±4.78 yr.; 180.5±5.42 cm; 76.5±7.94 kg) of the highest Slovak football league. The correlation between 30 m performance and average eccentric hamstring strength has been -0.0826. The correlation suggests that the sprint speed and eccentric strength of the hamstrings have not been associated 0 (t=-0.5619; df=46; p=0.5769). Correlation between 30 m performance and AVG/kg was -0.1317, indicating that the correlation between average weight and speed was not been significant. The eccentric strength has not been associated with a higher speed in the 30-m sprint test. However, more intervention studies are warranted.